Formação de professores para educação especial no Paraná : cursos de pedagogia, pós-graduações lato sensu e políticas públicas - Harlos, Franco Ezequiel (2015)
The present research aimed to analyze the consonance between some of the courses (Pedagogy and lato sensu graduate programs) adopted in Paraná for the education of teachers aiming performance with students that fit Special Education’s target audience (SETA) and the current organizational and conceptual structure of Brazilian Special Education, in what concerns the teacher profile that is demanded by such structure. Therefore, documentary research was adopted, guided by actions subdivided into three phases, namely: I. analysis of 30 documents that delimitate the current organizational and conceptual structure of Brazilian Special Education, compiled from the Ministry of Education homepage; II. analysis of 35 political pedagogical projects collected from Higher Education Institutions (HEI) homepages regarding Pedagogy programs; III. analysis of data about the structuring of 63 lato sensu graduate programs in Special Education, identified in HEI homepages. In phase I, it was concluded that the current organizational and conceptual structure of Special Education creates a demand for polyvalent teachers, with broad technical and methodological knowledge for performance with all the segments of SETA students. In phase II, it was concluded that 95.3% of the analyzed lato sensu graduate programs are structured without a foreseen requirement of teacher internship in Special Education; that 74.6% of these present a multifocal model (which focuses all segments of SETA students); that these courses present an average of 397.2 hours of duration and 13.19 subjects; that 15.87% of these courses present programs composed of 50% or over 50% of subjects that do not discuss Special Education. In phase III, it was concluded that in 85.8% of the analyzed Pedagogy programs there is no foreseen requirement of performance with SETA in the curriculum’s mandatory internships; that in 95.4% of these courses, Special Education is mentioned exclusively in the subjects specifically directed to it; that these courses present an average of 2.68 subjects directly related to Special Education, an average of 83.6 hours of workload dedicated specifically to Special Education and 67.6 hours to the teaching of Libras (Brazilian Sign Language). The triangulation of the data incited the inference that the current organizational and conceptual structure of Brazilian Special Education has reconfigured the teacher profile demanded for performance with SETA students, expanding and making more complex the knowledge and functions that shall be associated with the teacher. Concomitantly, such structure has perpetuated and favored models of formation of teachers that overly restrict the time dedicated to professional practice and to the learning of indispensable methodologies and techniques. Thus, a transformation in Pedagogy and lato sensu graduate programs in Special Education is suggested, with official guidelines which determine a basic structuring for the courses that intend to professionally capacitate for performance in Special Education and that establish that in such courses foreseen curriculum internships with SETA shall be mandatory.